Quality Concerns in School Education - Sharan, Shankar (JOURNAL OF INDIAN EDUCATION, 2015)
This paper is based on the observations and experiences gathered during a three-month teaching assignment at a Kendriya Vidyalaya in a small town of eastern India. It was precisely the quality concerns that repeatedly troubled this author, since the school being a Kendriya Vidyalaya it had all the necessary amenities that anyone can ask for in a secondary school. It is even more troubling because the prevalent educational discourses devote more time to material requirements for education and little to the quality/ essence of education.